Pectin and gastric pH interactively affect DHA-rich emulsion in vitro digestion microstructure, digestibility and bioaccessibility. (March 2018) - Lin, Xinjie; Wright, Amanda J.
Abstract: Lipid digestibility and bioaccessibility (i.e. solubilization) may be impacted by various factors. For example, dietary fibres may interact with lipids and other digestive molecules during gastrointestinal digestion and gastric pH may impact lipid droplet microstructure. Thus, these parameters may have implications for the release and uptake of bioactive fatty acids such as DHA. This study investigated how apple pectin (0.00, 5.68, or 100.00 mg/5.0 g emulsion), combined with variable gastric pH (2.0, 3.0 or 4.8), impacted the in vitro digestion of a DHA-rich algal oil lecithin-stabilized emulsion (10:1.2:88.8 oil:lecithin:water, D3, 2 = 0.137 ± 0.001 nm). Low gastric pH (2.0 and 3.0) induced severe emulsion destabilization. However, the addition of a low-level of pectin (5.68 mg/5.0 g emulsion) reduced the destabilization at pH 3.0. Small lipid droplets, maintained either by this low-level of pectin at pH 3.0 or by a higher gastric pH (4.8), were associated with greater early (p < 0.05), but not eventual (p > 0.05) duodenal lipolysis (pH 7.0) and higher DHA bioaccessibility (>69%, p < 0.05). Samples containing 100.00 mg pectin/5.0 g emulsion had the lowest overall lipolysis and DHA bioaccessibility across all pH values (p < 0.05). Therefore, pectin content and gastric pH interactively impacted emulsion digestion. The presence of applesauce, matched for pectin concentration, further destabilized the emulsion and limited lipid digestibility and DHA bioaccessibility, compared to the pectin-only samples. Overall, a stable emulsion microstructure during gastric digestion promoted in vitro lipid digestibility and DHA bioaccessibility. Graphical abstract: Highlights: Highly acidic gastric pH destabilized a soy lecithin-stabilized DHA-rich emulsion. Low pectin concentration retained emulsion microstructure at gastric pH 3.0. A high level of pectin reduced lipolysis and DHA bioaccessibility, regardless of gastric pH. Smaller droplets were associated with duodenal lipolysis and DHA bioaccessibility. Pectin-containing applesauce further limited lipid digestion and bioaccessibility.